The Pengaruh Dukungan Organisasi Terhadap Iklim Keselamatan Pasien di Rumah Sakit Restu Ibu Balikpapan - Heriyati, Heriyati Heriyati; H.M. SInaga, Alexander (Window of Health : Jurnal Kesehatan, 2018)
The patient's safety climate emerges as an important factor in healthcare organizations. The purpose of this study is to analyze the effects of fairness, leader support and reward for the patient's safety climate. This research is a quantitative research using analytical survey design with cross sectional study approach. The sample of this research as many as 187 respondents who are staffs in Restu Ibu Hospital of Balikpapan with purposive sampling method. Data were analyzed by using linear regression test. The results show that there is an influence of fairness, support of leaderss and reward for patient safety climate. The results of this study are expected to be an input to improve patient safety climate more specifically to pay attention to the awarding of employees.